The expanding horizon : a geographical commentary upon routes, records, observations & opinions contained in selected documents concerning travel at the Cape, 1750-1800 - Forbes, Vernon S (Vernon Siegfried) (Rhodes University, Faculty of Science, Department of Geography, 1958)
This study seeks to provide a geographical commentary upon documents relating to travel in the Cape during the second half of the eighteenth century. These documents include not only books of travel, but also travel journals, letters and maps both published and unpublished. They have been examined in the first place to ascertain what light they throw on the evolution of geographical ideas concerning the phenomena now capable of classification under the broad heading of physical geography. Secondly the have been viewed as part of the geography of travel and exploration which deals with routes, the identification of places, the explanation of place-names and the evolution of the map, or in its absence, of the mental picture of the regions reported on. Historical events are also considered, for the geographer can no more afford to ignore history than the historian dare cast a blind eye upon geography.
Keywords: Travelers -- South Africa; South Africa -- Description and travel -- Early works to 1800